2021
DOI: 10.1093/mnras/stab3450
|View full text |Cite
|
Sign up to set email alerts
|

A survey for variable young stars with small telescopes – V. Analysis of TX Ori, V505 Ori, and V510 Ori, the HST ULLYSES targets in the σ Ori cluster

Abstract: Investigations of the formation of young stellar objects (YSOs) and planets require the detailed analysis of individual sources as well as statistical analysis of a larger number of objects. The Hubble UV Legacy Library of Young Stars as Essential Standards (ULLYSES) project provides such a unique opportunity by establishing a UV spectroscopic library of young high- and low-mass stars in the local universe. Here we analyse optical photometry of the three ULLYSES targets (TX Ori, V505 Ori, V510 Ori) and other Y… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
(89 reference statements)
1
3
0
Order By: Relevance
“…The estimated WM in parallax, * m a , and μ δ are 2.45 ± 0.12 mas, 1.23 ± 0.91 mas yr −1 , and -0.47 ± 0.80 mas yr −1 , respectively. From the median parallax we find the distance to the cluster to be 408 ± 8 pc, which is consistent with other Gaia-based distance estimated in Monteiro et al (2020) and Froebrich et al (2022).…”
Section: Member Selection Using Gaia Dr3supporting
confidence: 90%
See 1 more Smart Citation
“…The estimated WM in parallax, * m a , and μ δ are 2.45 ± 0.12 mas, 1.23 ± 0.91 mas yr −1 , and -0.47 ± 0.80 mas yr −1 , respectively. From the median parallax we find the distance to the cluster to be 408 ± 8 pc, which is consistent with other Gaia-based distance estimated in Monteiro et al (2020) and Froebrich et al (2022).…”
Section: Member Selection Using Gaia Dr3supporting
confidence: 90%
“…This region was first described by Garrison (1967) and later several photometric and spectroscopic studies have been carried out (Béjar et al 1999(Béjar et al , 2001Zapatero Osorio et al 2002;Kenyon et al 2005;Lodieu et al 2009;Peña Ramírez et al 2012;Hernández et al 2014;Zapatero Osorio et al 2017;Caballero et al 2019). The kinematic study by Froebrich et al (2022), using photometric and astrometric data from Gaia EDR3, showed that the cluster has a main population of young stellar objects at ∼403 pc. The cluster is affected by almost negligible extinction A V < 1 mag (Lee 1968;Béjar et al 2004), which enables identification of the coolest objects in the region.…”
Section: Introductionmentioning
confidence: 90%
“…However, for several of the clusters our values are in agreement with previous works using earlier versions of Gaia data, such as DR2 and EDR3. These are for example: NGC 1333 and IC 348 (Pavlidou et al 2021); M 42 and other regions in the Orion complex (Chen et al 2020); 𝜎-Ori (Froebrich et al 2022); IC 5070 (Kuhn et al 2020);IC 1396(Pelayo-Baldárrago et al 2023. Several of our regions are also included in Mendigutía et al (2022).…”
Section: Discussionmentioning
confidence: 99%
“…This field has already been analysed in detail in Froebrich et al (2022) using GaiaEDR3 data. Hence, our results are very similar to these.…”
Section: 𝜎-Orimentioning
confidence: 99%

Penellope

Sperling,
Eislöffel,
Manara
et al. 2024
A&A